EFFECT OF DIFFERENT pH ON GROWTH PERFORMANCE Gracilaria changii - Nur Indah Sari Arrbit (LPPM Universitas Terbuka, 2022)
The phenomenon of ocean acidification is a condition of decreasing ocean pH due to carbon dioxide absorption. Ocean acidification has a negative impact on marine organisms, one of which is seaweed. This study aims to determine the growth performance of Gracilaria changii seaweed against different pH. This research was conducted for 30 days at the Multitrophic Laboratory and water quality Research Activity Center, Hasanuddin University Makassar. The experimental design carried out in this study was a completely randomized design (CRD) in which there were four treatments. The first treatment (P1) with a pH of 3.5, the second treatment (P2) with a pH of 5.5, the third treatment (P3) used a pH of 9.5 and the control treatment was pH 8 (P0). The test parameters in this research are daily weight growth, pigment content and water quality. Data analysis used ANOVA analysis of variance with further W-Tukey test. The results of this study were the growth performance of Gracilaria sp. the best among all treatments is the pH 5.50 treatment where the growth rate is 11.49%. The optimum pH range for seaweed, especially Gracilaria sp. ie 6-8. But at pH 5.5 it can still be tolerated and in this study.